Acyclic Acetals in Propylene Carbonate-Based Electrolytes for Advanced and Safer Graphite-Based Lithium Ion Batteries. Issue 4 (13th February 2020) - Atik, J.; Röser, S.; Wagner, R.; Berghus, D.; Winter, M.; Cekic-Laskovic, I.
Abstract : In this work, we investigate the electrochemical and safety performance of the glyoxalic acyclic acetals, namely 1, 1, 2, 2-tetramethoxyethane (TME) and 1, 1, 2, 2 tetraethoxyethane (TEE) as substituted solvents for linear organic carbonates in propylene carbonate (PC)-based electrolytes in LiNi0.6 Mn0.2 Co0.2 O2 ∣∣graphite cells. By means of conductivity measurements and under consideration of PC-intercalation suppression, an optimized electrolyte was formulated with excellent thermal properties and electrochemical performance. The optimized electrolyte shows excellent cycling performance at the level of established organic carbonate-based electrolyte consisted ethylene carbonate, ethyl methyl carbonate and with lithium hexafluorophosphate as conducting salt with an extended operating cycling temperature window, good C-rate behavior and promising safety properties, clearly demonstrating the application potential of this new solvent class for lithium ion battery electrolytes.